A comparison of the respective advantages and disadvantages of companies and trusts as vehicles for estate planning - Mhlongo, Nokukhanya (My University, 2018)
Estate planning is often thought of to be for the purposes of minimising estate duty only. This is but one of the intentions of estate planning. Being able to provide capital and income for beneficiaries before and after death is usually the main objective of creating an estate plan. It therefore follows that liquidity after death is an imperative part of the estate plan. In this research, the formation of a trust or company as an estate planning tool will be discussed. The advantages and disadvantages of both will be explored. There will also be a discussion around methods which can be used to transfer assets into either a trust or a company. The income tax, capital gains tax, donations tax and estate duty considerations will be considered. Over the years, the fiscus has been closing more and more loopholes for tax planning. It has therefore become imperative to determine whether the above-mentioned tools, being a trust and a company, for estate planning are still relevant in current economic times. This research therefore seeks to provide a comparative study between using a trust, a company or a combination of both a trust and a company for estate planning purposes.
A research report submitted to the Faculty of Commerce, Law and Management in partial fulfilment of the requirements for the degree of Master of Commerce in the field of Taxation,2018